Coexistence of ectopic tubal pregnancy with serous tubal intraepithelial carcinoma: A rare case report with review of literature - Shirish Sahebrao Chandanwale; Yesha Parimalbhai Lad; Padmakar Rajabhau Bardapurkar; Archana Chirag Buch (Wolters Kluwer Medknow Publications, 2022)
Serous tubal intraepithelial carcinoma is a precursor lesion for high-grade pelvic serous carcinoma. The incidence is 0.6%-6% in tubectomy specimens of women who are BRCA-1,2 positive or have a strong family history of breast or ovarian cancer. STIC in women who do not have BRCA-1,2 mutations or concomitant high-grade serous carcinoma is exceedingly rare. Ectopic tubal gestation coexisting with serous tubal intraepithelial carcinoma is very rarely reported. These lesions pose considerable difficulty in the diagnosis. A combination of histology and immunohistochemical expression p53 and ki67 substantially improves the reproducibility of the diagnosis. Diagnosing these lesions will help identify potential at risk patients and their families for carcinoma. Adequate prolonged follow-up for incidental serous tubal intraepithelial carcinoma is the mainstay. We report one such case of a 31-year-old female who was operated for the right tubal gestation and found to have serous tubal intraepithelial carcinoma.